The Role of Brand Personality: Dimensions of Online Customer Review on Online Booking Intention at Star Hotels in Malang City - Aditiya Pratama Nugroho; DC Kuswardani; Adijati Utaminingsih (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This activity has a research objective to analyze the role of brand personality variables as mediation and the independent variables negative review, visual cue, and review length on booking intention. The method used is quantitative with a purposive sampling technique, in collecting data using a questionnaire statement, the data collected is 190 respondents. The test used is descriptive analysis and also the Structural Equation Model (SEM) using smart PLS 3.2.9 software. The results show that negative reviews, visual cues, and review length positively and significantly affect brand personality and booking intention. Furthermore, the effect of brand personality on booking intention also found positive and significant results. The results of the indirect effect show that negative reviews, visual cues, and review length through Brand personality on booking intention have a positive and significant effect, meaning that brand personality can mediate the relationship between negative reviews, visual cues, and review length on booking intention.